Worms in smallholder livestock systems: Technologies and practices that make a difference - Gray, G.D.; Connell, J.G.; Phimphachanhvongsod, V. (Elsevier, 2012)
Australian scientists, in partnership with Asian, African and Pacific nations have longstanding interests in applied research on helminth parasite control. Many technologies and practices have been successfully developed to control the parasite problems of smallholder and emerging farmers. This wide range extends from simple herbal remedies to complex, integrated use of chemicals, feeding and breeding. In many cases widespread adoption has been limited by lack of technical support, poor access to input markets and lack of incentives for poorer farmers to seek out and pay for innovations. A further new approach may be required that encompasses the wider production and market environment. The biological, social and economic context of each ‘emerging farming system’ is different and matching technologies to each system requires sound understanding of farmer needs and requirements. Thus, it is essential that farmers, extension workers, and scientists jointly decide what technologies to try, what results mean and, if successful, how to sustain their use. In one Asian example a range of technologies were considered for pig, large ruminant and goat production and parasite control through a participatory process which was also used to agree on what determines sustainability beyond testing. The criteria use to screen technologies and practices were a) continued availability of inputs including dewormers, b) dependence on related innovations (e.g. weaning or fencing) and c) degree of community organisation required (e.g. control of breeding or communal grazing). On this basis deworming with chemicals, especially for Toxacara infection in cattle and buffalo calves following on from supplementary feeding with forages were the most feasible entry points. Further interventions were dependent on changes to the production system, including the introduction of weaning and controlled breeding. Further, the incentives for these production changes could not exist without improved market access and market signals for improved weight and condition. Examples such as this point to the need for stronger multidisciplinary and participatory approaches to parasite control.